Variations on the canon : essays on music from Bach to Boulez in honor of Charles Rosen on his eightieth birthday - Curry, Robert, 1952 September 26-; Gable, David, 1955-; Marshall, Robert Lewis (Eastman studies in music, 2008)
Inspired in its liveliness and variety of critical approaches by Charles Rosen's challenging work, Variations on the Canon offers original essays by some of the world's most eminent musical scholars. Contributors address such issues as style and compositi.